Pharmacy services during COVID-19 pandemic: experience from a tertiary care teaching hospital in Pakistan - Kashif Hussain; Gul Ambreen; Mehreen Muzammil; Syed Shamim Raza; Umer Ali (Taylor & Francis Group, 2020)
The coronavirus disease 19 (COVID-19) is rapidly spreading across the world. Pharmacy services play a vital role in public health in preventing and containing the COVID-19 pandemic. All over the world, especially in the developed countries pharmacists have responded smartly and speedily for public health, such as establishing professional protective and service guidance for pharmacy staff and services, creating and updating drug formularies, addressing the issues of drug shortages, providing public education for prevention and management of infection, contributing in drug evaluation and clinical trials. In this commentary, we review the exclusive demands from pharmacy services in Pakistan during coronavirus disease 2019 pandemic and sharing the responses of our hospital pharmacy to these demands and needs with the international pharmacy community, especially of the low and middle-income countries like Pakistan.